Assessment of function-technological and rheological parameters of consistency stabilisers for dairy protein-fat systems for the production of semi-smoked sausages - Rudiuk, Vitaliy; Pasichnyi, Vasyl (Technology audit and production reserves, 2023)
During the past few years, the world community has faced a number of problems related to the delivery and storage of milk and milk products. In particular, the situation provoked by quarantine restrictions in various countries of the world forces to look for solutions regarding the use of non-traditional raw materials for the production of classic or similar food products. As a result, it is quite promising to use dairy products with extended shelf life, in particular, dry milk concentrates as the main protein carriers for the production of stable protein-fat systems. The use of dry milk proteins makes it possible to manufacture restored structural products that can be used as an alternative to classic ones. Therefore, the object of research is food components of various origins, in particular food modified starches, food fibers and their modifications, hydrocolloids. Characteristic indicators of viscosity with increasing shear stress were determined for 5 % solutions of modified starches of various types after brewing at a temperature of 80 °C. It was found that when the shear stress increases to a value of 200 Pa, there is a significant decrease in viscosity, which generally characterizes them as structural systems. The functional and technological indicators of wheat (VF-200), bamboo (BAF-200) food fibers (fiber length 200 microns) and carboxyl methyl cellulose (CMC) were studied. Increased functional and technological capabilities of CMC compared to dietary fibers were revealed. The kinetics of swelling of dietary fibers and CMC were studied, while the period of maximum intensification of the process, which is between 5 and 15 minutes, was determined. The maximum value of the swelling coefficient is characteristic for CMC 4.4±0.04, for wheat fiber 4.01±0.06, for bamboo fiber 3.81±0.05. Using the method of mathematical and statistical processing of experimental data, optimization of concentration and technological modes was carried out to achieve maximum hydration and strength of iota-carrageenan gel. It was determined that at a concentration of 1 % during brewing at 80 °C and a time of 5 min. high enough gel strength can be achieved for optimum consistency in the overall system. The result of the work is a comprehensive study of the functional technological characteristics of food additives that will form the consistency of a structural protein-fat product of the cheese type, which can be used in sausage products as a filler, with the aim of improving the organoleptic, structural-mechanical and nutritional values of the finished products.